This disabled body: an authoethnographic study of disability in post apartheid South Africa - Mata, Siwongiwe (Social Anthropology, 2025)
Disability lies at the heart of a complex framework of knowledge and identity in post-apartheid South Africa. In this autoethnographic study, personal reflections on my history as a queer, Black, physically disabled individual are retold and compared to her current personal narratives to answer questions about disability in a contemporary South African context. Comparing my current experiences to my past, the question of how stigma manifests when considering the relationship between the disabled, other disabled people and the able-bodied is explored through looking at my relationship with my assistive devices. This catapults the reader into understanding how bureaucracy emerges in disabled life, as the assistive devices can be viewed as mediators of the relationship between the disabled and the world. The question of what community means for disabled people is explored in an attempt to articulate the complexities and nuances of disabled identity. Most hegemonic disability theory often does not account for the complexities and flexibility of the everyday life of a disabled individual. Reliant on memory, this study illustrates how crucial personal and intersectional reflections are in establishing how stigma lives in the stigmatiser and the stigmatised in different contexts, shaped by time and experiences. Further, this thesis demonstrates the value of considering events across time and that ableist interactions and experiences are not static but are dynamic and are constantly reshaping social relations.